ANALISIS BIAYA KUALITAS DALAM PELAKSANAAN PENGENDALIAN MUTU DI PT XYZ GRESIK - Ariasna, Ketut (Fakultas Ekonomi Universitas Gresik, 2020)
This study aims to determine and evaluate the extent to which quality control costs at PT XYZ Gresik.This research method uses qualitative research methods by collecting data, conducting observations, interviews and triangulation.The results showed that the quality costs incurred by PT XYZ Gresik during 2016 - 2018 amounted to 4.11% of total sales. While the analysis shows that quality cost efficiency has not reached the measurement standard in the theory used by researchers even though quality control at PT XYZ Gresik has been good because of the aspect of cost reporting, the quality has not been maximized